KAJIAN STRUKTUR KOMUNITAS MOLUSKA DI PANTAI REKLAMASI TELUK MANADO - Kenjiro Y. R. Paat; Frans Lumuindong; Erly Y. Kaligis; Farnis B. Boneka; Fitje Losung; Alex D. Kambey (JURNAL PESISIR DAN LAUT TROPIS, 2022)
This study aims to determine the increase or decrease in mollusk species on the reclamation coast and also to determine the development of the mollusk community structure and its activities in the intertidal zone of the reclamation coast of Manado Bay. Based on the results of sampling obtained 15 species from 7 families. The mollusk density value is 58.30 Ind/m2. The diversity index obtained from the results of the analysis is classified as low, namely H' = 1.684. The dominance value obtained from the results of data analysis is low, namely C = 0.37. The highest species frequency value was found in the Cellana radiata species with a value of 0.60 and the lowest in the Menathais tuberosa species, Drupa rubusidaeus, Drupa ricinus, Nerita polita, with a 0.03 value. The relatively high significance index was found in the species Saccostrea cuccullata with a value of 106.28%, while the lowest value was found in the species Menathais tuberosa and Drupa ricinus with a value of 1.24%. The response and adaptation ability of mollusks in the intertidal zone varies based on the size of the species and their adaptability. The reclamation beach of Manado Bay has a temperature of 29.5 °C, salinity of 30 0/00, and the obtained pH is 8. Based on these results, the reclamation coastal waters of Manado Bay are classified as good for mollusk life. Keywords: Community Structure, Mollusk, Reclamation. ABSTRAK Penelitian ini bertujuan untuk mengetahui bertambah atau berkurangnya spesies moluska di pantai reklamasi dan juga mengetahui perkembangan struktur komunitas moluska serta aktivitasnya di zona intertidal pantai reklamasi Teluk Manado. Berdasarkan hasil pengambilan sampel diperoleh 15 spesies dari 7 famili. Nilai kepadatan moluska sebesar 58,30 Ind/m2. Indeks keanekaragaman yang diperoleh dari hasil analisis tergolong rendah yaitu H’ = 1,684. Nilai dominasi yang diperoleh dari hasil analisis data tergolong rendah yaitu C = 0,37. Nilai frekuensi spesies tertinggi pada terdapat pada spesies Cellana radiata dengan nilai 0,60 dan terrendah pada spesies Menathais tuberosa, Drupa rubusidaeus, Drupa ricinus, Nerita polita, dengan nilai 0,03. Indeks nilai penting relatif tinggi terdapat pada spesies Saccostrea cuccullata dengan nilai 106,28% sedangkan nilai terrendah pada spesies Menathais tuberosa dan Drupa ricinus dengan nilai 1,24%. Kemampuan respon dan adaptasi moluska di zona intertidal berbeda-beda berdasarkan ukuran besar kecilnya jenis serta kemampuan adaptasinya. Pantai reklamasi Teluk Manado memiliki suhu 29,5 °C, salintas 30 0/00, dan pH yang diperoleh yaitu 8. Berdasarkan hasil tersebut perairan pantai reklamasi Teluk Manado tergolong baik untuk kehidupan moluska. Kata Kunci: Struktur Komunitas, Moluska, Reklamasi